2020
DOI: 10.1016/j.abd.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on the treatment of alopecia areata – Brazilian Society of Dermatology

Abstract: Background Alopecia areata is a highly frequent disease with an impact on quality of life and several treatment options with little clinical confirmatory evidence. Objective To disseminate the recommendations of Brazilian dermatologists with expertise in the treatment of alopecia areata. Methods Eight specialists with expertise in alopecia areata from different university centers were appointed by the Brazilian Society of Dermatology to reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 93 publications
3
64
0
7
Order By: Relevance
“…Combination of corticosteroids was most common among patients with moderate AA which is consistent with recommendations to prescribe topical as first-line treatment for cases and the ineffectiveness of topical or injectable corticosteroids alone in more severe types of AA [3,16]. Combination with or solo immunomodulator was almost exclusive to patients with severe AA, likely due to concerns about treatment side effects [17].…”
Section: Discussionsupporting
confidence: 63%
“…Combination of corticosteroids was most common among patients with moderate AA which is consistent with recommendations to prescribe topical as first-line treatment for cases and the ineffectiveness of topical or injectable corticosteroids alone in more severe types of AA [3,16]. Combination with or solo immunomodulator was almost exclusive to patients with severe AA, likely due to concerns about treatment side effects [17].…”
Section: Discussionsupporting
confidence: 63%
“…A literature review found two overseas AA treatment guidelines and two expert consensus reports 2–5 . All of them recommend topical corticosteroids, intralesional corticosteroid injections, and contact immunotherapy as treatment modalities (Table 1).…”
Section: Current Management Strategymentioning
confidence: 99%
“…Unlike topicals, ILTA bypasses the epidermis when injected, achieving direct access to the HF. 14 High-quality controlled studies regarding the use of ILTA in AA are scarce. A meta-analysis concluded that 5 mg/mL and 10 mg/mL of ILTA diluted in NS were equally effective (80.9% [P<.05] vs 76.4% [P<.005], respectively).…”
Section: Commentmentioning
confidence: 99%